Assessment of constraints and opportunities in small-scale beef cattle fattening business: Evidence from the West Hararghe Zone of Ethiopia - Adunea Dinku (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
The study was conducted in Gemachis and Doba districts of West Hararghe Zone of Ethiopia to investigate the major constraints and opportunities of small-scale cattle fattening practices, and identify cattle selection criteria used for fattening purpose. Multi stage sampling procedure was employed to obtain a total of 171 cattle fatteners. The questionnaire based formal survey was conducted using pre tested semi-structured questioners to generate quantitative data. Besides, qualitative data were gathered through group discussions and key informant interviews to corroborate the survey data. Secondary date was obtained from published and unpublished documents. Data was analyzed using descriptive statistics, inferential statistics, and rank index.